Ligation of porcine Fc gamma receptor III inhibits levels of antiviral cytokine in response to PRRSV infection in vitro. (April 2016) - Zhang, Liujun; Chen, Jing; Wang, Dongmei; Li, Nana; Qin, Yunjie; Du, Dongying; Yang, Mingfan; Xia, Pingan
Abstract: PRRSV infection ADE facilitates the attachment and internalization of the virus onto macrophages through Fc receptor-mediated endocytosis. FcγR III is the activating receptor with a tyrosine-based activating motif (ITAM) in its cytoplasmic tail, where up-regulates phagocytosis. However, porcine FcγR III's role in the antiviral immune response to PRRSV infection has not been studied. In this study, our results indicated that selective activation of porcine FcγR III in PAM cells down-regulated significantly mRNA levels of IFN-α and TNF-α post-pretreatment, and up-regulated significantly mRNA level of IL-10 post-pretreatment, suggesting that porcine FcγR III signal can inhibit the transcriptional levels of innate antiviral cytokine in host cells. Simultaneously, PRRSV infection assay mediated by FcγR III indicated that selective activation of porcine FcγR III in PAM cells inhibited significantly mRNA levels of IFN-α and TNF-α, and enhanced significantly mRNA level of IL-10, and increased significantly viral mRNA levels, in response to PRRSV infection, suggesting that FcγR III ligation can inhibit the antiviral immune response to PRRSV infection. These results elucidated that the one mechanism of PRRSV-ADE regulated via porcine FcγRIII may be by decreasing antiviral cytokine levels, facilitating viral replication. Highlights: PRRSV infection induces antiviral response in PAM. Specific activation of FcγR III can influence the innate antiviral response. Ligation of FcγR III inhibits levels of antiviral cytokine in PRRSV infection. Ligation of FcγR III enhances viral replication in PRRSV infection.